2020
DOI: 10.1111/papr.12855
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence Lacking to Guide Clinical Practice for Spinal Cord Stimulation in the Treatment of Neuropathic Pain in Spinal Cord Injury: A Review of the Literature and a Proposal for Future Study

Abstract: Background/Objective Chronic pain is commonly reported in individuals with spinal cord injuries (SCIs), with recent prevalence reported as high as 80%. Uncontrolled pain is known to decrease quality of life, attenuate mood, and impact sleep. Spinal cord stimulation (SCS) for the treatment of refractory pain was first used in the SCI population in 1972. To date there have been no randomized controlled trials examining the effect of SCS on neuropathic pain post‐SCI. A literature review in 2009 identified 27 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…Fourteen days post-lesion is considered chronic neuropathic pain in most pre-clinical studies where chronic neuropathic pain has been defined as that which persisted 14 days post-lesion; 30-40 min SCS stimulation paradigms have been tested in these studies [50][51][52]. On day 3 after peripheral nerve injury, the central sensitization process is not as robust as it is after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen days post-lesion is considered chronic neuropathic pain in most pre-clinical studies where chronic neuropathic pain has been defined as that which persisted 14 days post-lesion; 30-40 min SCS stimulation paradigms have been tested in these studies [50][51][52]. On day 3 after peripheral nerve injury, the central sensitization process is not as robust as it is after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence for its use in neuropathic pain after SCI has not been demonstrated in randomized controlled trials (RCTs). 117 Epidural electrical stimulation (EES) was incidentally found to improve motor function in patients suffering from MS, with an original premise to reduce neuropathic pain. 118 The mechanisms by which the stimulation parameters can enable stepping and standing, akin to central pattern generators of locomotion, remain elusive.…”
Section: Stimulation Adjuncts To Spinal Rehabilitationmentioning
confidence: 99%
“…A literature review about the clinical practice of SCS for treatment of SCI-induced neuropathic pain by searching MEDLINE and EMBASE databases showed that 9 out of 22 case studies reported more than 50% pain relief was achieved by conventional stimulation, 3 out of 22 reported 30-80% pain reduction was obtained by high-frequency stimulation, and 1 out of 22 reported 30% pain score was reduced by burst stimulation. Although the quality of these case studies was low, they support the pain-relief efficacy and safety of SCS in SCI and point out the possibility of clinical practice of SCS for the management of NP after SCI [ 87 ]. Together with the preclinical study of SCS in the SCI pain model, which reported that a low-frequency (10-25 Hz) stimulation was associated with neural progenitor activation in the spinal cord and led to long-lasting analgesia [ 62 ], conventional SCS with lower frequency might be more efficient in SCI patients.…”
Section: Clinical Application and Side Effect Concernsmentioning
confidence: 99%